2017
DOI: 10.1177/0972262916681249
|View full text |Cite
|
Sign up to set email alerts
|

Crafting Responsible Management Practices in Business School Learning Outcomes: An Indian Case Study

Abstract: Management education is increasingly facing societal demands for becoming responsible business. Many management institutions have therefore become involved in embedding sustainable development as part of responsible management education into their academic system. This was also due to use of ‘responsible management’ as one of the important criteria in the international accreditation process and thus leading to greater acceptability amongst its target audience. The United Nations (UN)-supported Principles for R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 99 publications
1
9
0
2
Order By: Relevance
“…More studies on the practical implementation of PRME in Business Schools, and the reasons for why some Business Schools resisted the initiative were called for (Arruda Filho 2017). The geographical context in which PRME works was an important factor in articulating future forms of research (Alcaraz and Thiruvattal 2010;Young and Nagpal 2013;Barber et al 2014;Louw 2015;Oranges Cezarino et al 2016;Arruda Filho 2017;Beddewela et al 2017;Décamps et al 2017;Gentile 2017;Greenberg et al 2017;Kolb et al 2017;Singhal et al 2017;Millar and Price 2018). Studies on PRME outside wealthy, western business school contexts were called for (Verbos and Humphries 2015a, b;Painter-Morland et al 2016).…”
Section: Organizing For Responsible Management Education (Orme)mentioning
confidence: 99%
See 1 more Smart Citation
“…More studies on the practical implementation of PRME in Business Schools, and the reasons for why some Business Schools resisted the initiative were called for (Arruda Filho 2017). The geographical context in which PRME works was an important factor in articulating future forms of research (Alcaraz and Thiruvattal 2010;Young and Nagpal 2013;Barber et al 2014;Louw 2015;Oranges Cezarino et al 2016;Arruda Filho 2017;Beddewela et al 2017;Décamps et al 2017;Gentile 2017;Greenberg et al 2017;Kolb et al 2017;Singhal et al 2017;Millar and Price 2018). Studies on PRME outside wealthy, western business school contexts were called for (Verbos and Humphries 2015a, b;Painter-Morland et al 2016).…”
Section: Organizing For Responsible Management Education (Orme)mentioning
confidence: 99%
“…Others were concerned with critically appraising the nature of business curricula in order to determine the hidden challenges which emerge from trying to embed RIL in a management programme. Whereas some attempt to integrate PRME principles when drafting student learning outcomes (Singhal et al 2017), others have highlighted the 'profitfirst' mindset that is embedded in much entrepreneurship education can influence how the benefits of sustainabilityoriented programmes are perceived (Lourenco et al 2013). This concern is perhaps best articulated in Blasco's (2012) study of how the 'hidden curriculum' of management education problematizes attempts to mainstream responsible management learning.…”
Section: Responsible Individual Learning (Ril)mentioning
confidence: 99%
“…Filho (2017) found that the integration of SD into academic curricula of a Brazilian business school, as suggested by the PRME and the UN Sustainable Development Agenda 2030, requires greater involvement of students to raise awareness about their role in society and participation as protagonists in the changes the world needs. Singhal et al (2017) aimed at understanding the PRME implementation process and the challenges they posed to the institutions. They looked, in particular, into a management course in an HEI in north India.…”
Section: Teaching About Sustainable Development In Business Sciencesaccounting and Managementmentioning
confidence: 99%
“…This was also due to use of ‘responsible management’ as one of the important criteria in the international accreditation process and thus leading to greater acceptability among its target audience. The UN-supported PRME initiative is an important catalyst for the transformation of management education in this direction (Singhal, Suryawanshi, & Mittal, 2017).…”
Section: Sustainability In Management Educationmentioning
confidence: 99%